AN ANALYSIS OF STUDENTS’ MOTIVATION IN LEARNING ENGLISH DURING PANDEMIC COVID-19 AT THE EIGHTH GRADE STUDENTS’ OF SMP NEGERI 3 SATU ATAP ANDAM DEWI IN 2020/2021 ACADEMIC YEAR - srimaharani tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: This research aim to know students motivation in learning English during pandemic Covid-19 at the Eighth grade students of SMP Negeri 3 Satu Atap Andam Dewi 2020/2021 Academic Year. Informant in this research are 34. 28 students class A, 1 English teacher in SMP Negeri 3 Satu Atap Andam Dewi and 5 parents of students. based on the observation was done before, researcher founded almost of the students are motivated in learning English before the pandemic with percentage 90% and after Covid-19 was came just 25% are motivated in learning English and 75% is not motivated in learning English during Covid-19 pandemic its means Covid-19 made students are not motivated in learning English during this pandemic. Its showed Covid-19 made students at the eighth grade of SMP Negeri 3 Satu Atap Andam Dewi mostly not motivated in learning English during pandemic Covid-19 and the dominant factor is came from internal factor.Keywords: Motivation, Learning, Covid-19